2020
DOI: 10.3390/jcdd7030024
|View full text |Cite
|
Sign up to set email alerts
|

The Association of rs1898830 in Toll-Like Receptor 2 with Lipids and Blood Pressure

Abstract: Background and Objective: Toll-like receptors (TLRs) are important components of the innate immune system, involved in establishing immunity to infections. Apart from being implicated in immunity, numerous studies have reported that many TLRs, including TLR2, are involved in the pathogenesis of cardiovascular diseases and their risk factors. Since rs1898830 is associated with TLR2-mediated cellular activation, we aimed to study its association with CVD risk factors, such as lipid levels and hypertensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Although some TLR2 polymorphisms have been associated with the severity of viral infections, the contribution or mechanism of some of them have not been clearly described yet. The polymorphism rs18998830, known as -15,607 A/G and laid on the first intron of the TLR2 gene, has been significantly associated to severe bronchiolitis induced by RSV with fatalities in the Brazilian infants [70,71]. Another polymorphism in TLR2 gene, named as rs3804099, which is a synonymous SNPs in the single exon that means a C/T change coding Asn, was associated to a reduced proinflammatory cytokine secretion in hepatitis B virus chronic infection in a Chinese population [72].…”
Section: Pattern Recognition Receptors (Prrs)mentioning
confidence: 99%
“…Although some TLR2 polymorphisms have been associated with the severity of viral infections, the contribution or mechanism of some of them have not been clearly described yet. The polymorphism rs18998830, known as -15,607 A/G and laid on the first intron of the TLR2 gene, has been significantly associated to severe bronchiolitis induced by RSV with fatalities in the Brazilian infants [70,71]. Another polymorphism in TLR2 gene, named as rs3804099, which is a synonymous SNPs in the single exon that means a C/T change coding Asn, was associated to a reduced proinflammatory cytokine secretion in hepatitis B virus chronic infection in a Chinese population [72].…”
Section: Pattern Recognition Receptors (Prrs)mentioning
confidence: 99%
“…Human TLR2 is located in the long arm of chromosome 4 (4q31.3), including one coding exon and two non-coding exons. TLR2 has been recognized as a pathogenic factor implicated in tumorigenesis [ 5 , 16 ]. We observed a combined effect of a genetic variant of TLR2 since all four SNPs, rs1898830, rs3804100, rs3804099, and rs1339, showed a significant protective association against ALL, while Individuals carrying rs1337 C > G have a higher risk of ALL in the Saudi population.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our results, this SNP has been associated with the risk of different conditions in various populations. A study conducted in Lebanon revealed that G allele carriers were associated with decreased HDL-C levels and an increased risk of hypertension [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its functional significance is still unclear. However, it has been suggested that the small G allele may alter the expression or functionality of TLR2, resulting in an increase in the number and/or function of macrophages and endothelial cells, thereby enhancing the innate immune response, which is also involved in the pathophysiology of atherosclerosis [49,50]. The association of this variant with COVID-19 has not been studied.…”
Section: Tlrmentioning
confidence: 99%